Research Progress of New Anodes for Zinc Electrodeposition - TAO Yi, CHEN Bu-ming, HUANG Hui, GUO Zhong-cheng, HE Ya-peng (Cailiao Baohu, 2023)
Lead anodes are cheap and stable in acidic sulfate solution, so they are used to produce high purity zinc, but with reduced mineral quality, zinc electrolyte environment gets worse, many problems in traditional lead anodes limit their further development: including high oxygen evolution potential, cathode products pollution caused by anodic dissolution, poor mechanical properties. In order to solve these problems, the new anode was described in several different aspects in this paper: (1) Doping different elements (such as Ag, Ca, Co, RE, etc.) in the lead alloy could improve the alloy structure, enhance the electrocatalytic activity of the lead anode, and reduce the dissolution of lead in the electrolyte by adding substances. (2) Applying different processing techniques could enhance internal uniformity and dense degree of the lead alloy, and improve the mechanical properties of the alloy. (3) Applying other types of anodes, such as titanium-based anodes, aluminum-based anodes and carbon fiber anodes, could prevent the problems caused by the inherent properties of the lead alloy. Besides, while introducing different anode improvement methods, the preparation process and electrocatalytic mechanism were also mentioned, and the direction for the development trend of new anodes in the future was pointed out.